CRIMINAL PROTECTION AGAINST ELECTRONIC HARASSMENT DUE TO COVID-19 PANDEMIC: A COMPARATIVE STUDY BETWEEN IRAQI AND FRENCH LAW - Dhia Moslem Abd Alameer Ghaibi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Harassment or so-called bullying is an ancient phenomenon in societies. It has different causes that may be due to the individual himself or the individual’s environment. Harassment also has many types of material, such as beatings and assaults on people or moral contempt for the individual. Itis the resulting significant damage that may cause the individual and may lead to suicide or leave work.Because of the outbreak of Corona disease, another type of harassment has emerged towards the individuals affected, especially with social media. Electronic harassment has occurred towards these individuals. However, there are international conventions and recommendations urging states to establish laws to criminalizeharassment. We find that Iraqi legislation has a significant lack of criminal protection compared to French legislation, which continues to change and amend its rules to keep pace with developments in society.